ANALYSIS OF CORRELATION BETWEEN IL 6 GENE POLYMORPHISM (-174 G /C) AND CLASSIC RISK FACTORS IN PATIENTS WITH PREVIOUS MYOCARDIAL INFARCTIONS - A. V. Shevchenko; O. V. Golovanova; V. I. Konenkov; M. I. Voevoda; V. N. Maximov; O. M. Tolkacheva (Медицинская иммунология)
Abstract. We have carried out a prevalence analysis of IL6 (-174 G/C) gene promoter polymorphism and traditional cardiovascular risk factors in male patients living in the West Siberia that survived myocardial infarction (MI) in their anamnesis. Analysis of genotype frequencies have shown decrease of *-174 GG genotype in the patients with MI. Frequency of the same genotype is decreased among smoking patients as compared to healthy non-smokers. On other hand, an increased body weight and arterial pressure indexes increase is found in IL6*-174 G patients, versus healthy population. Hence, the analyzed IL6 (-174 G/C) polymorphism may be considered as an additional predisposition factor for development of vascular damage.